Impact of Failure of Noninvasive Ventilation on the Safety of Pediatric Tracheal Intubation*. Issue 10 (October 2020) - Emeriaud, Guillaume; Napolitano, Natalie; Polikoff, Lee; Giuliano, John; Toedt-Pingel, Iris; Miksa, Michael; Li, Simon; Bysani, Kris; Hsing, Deyin D.; Nett, Sholeen; Turner, David A.; Sanders, Ronald C.; et al.
Abstract : Objectives: Noninvasive ventilation is widely used to avoid tracheal intubation in critically ill children. The objective of this study was to assess whether noninvasive ventilation failure was associated with severe tracheal intubation-associated events and severe oxygen desaturation during tracheal intubation. Design: Prospective multicenter cohort study of consecutive intubated patients using the National Emergency Airway Registry for Children registry. Setting: Thirteen PICUs (in 12 institutions) in the United States and Canada. Patients: All patients undergoing tracheal intubation in participating sites were included. Noninvasive ventilation failure group included children with any use of high-flow nasal cannula, continuous positive airway pressure, or bilevel noninvasive ventilation in the 6 hours prior to tracheal intubation. Primary tracheal intubation group included children without exposure to noninvasive ventilation within 6 hours before tracheal intubation. Interventions: None. Measurements and Main Results: Severe tracheal intubation-associated events (cardiac arrest, esophageal intubation with delayed recognition, emesis with aspiration, hypotension requiring intervention, laryngospasm, pneumothorax, pneumomediastinum) and severe oxygen desaturation (< 70%) were recorded prospectively. The study included 956 tracheal intubation encounters; 424 tracheal intubations (44%) occurred after noninvasive ventilation failure, with a median of 13 hours (interquartile range, 4–38 hr) of noninvasive ventilation. Noninvasive ventilation failure group included more infants (47% vs 33%; p < 0.001) and patients with a respiratory diagnosis (56% vs 30%; p < 0.001). Noninvasive ventilation failure was not associated with severe tracheal intubation-associated events (5% vs 5% without noninvasive ventilation; p = 0.96) but was associated with severe desaturation (15% vs 9% without noninvasive ventilation; p = 0.005). After controlling for baseline differences, noninvasive ventilation failure was not independently associated with severe tracheal intubation-associated events ( p = 0.35) or severe desaturation ( p = 0.08). In the noninvasive ventilation failure group, higher FIO2 before tracheal intubation (≥ 70%) was associated with severe tracheal intubation-associated events. Conclusions: Critically ill children are frequently exposed to noninvasive ventilation before intubation. Noninvasive ventilation failure was not independently associated with severe tracheal intubation-associated events or severe oxygen desaturation compared to primary tracheal intubation. Abstract : Supplemental Digital Content is available in the text.